Perubahan kinerja keuangan dan operasional PT Link Net Tbk (LINK) pasca diakuisisi oleh EXCL - Susanto, Leonardo Christian; Halim, Kevin; Setiawan, Adrianus Bryan; Tandarto, Sefen Timothy; Wongso, Enrico; Linawati, Nanik (Journal of Accounting and Digital Finance, 2025)
This study aims to evaluate the impact of the acquisition of PT Link Net Tbk by XL Axiata and Axiata Group Berhad on the company’s financial and operational performance in the post-acquisition period. The main issue raised is the significant decline in performance following the acquisition, indicating that the integration strategy has not been effectively implemented. This research adopts a quantitative approach by analyzing financial indicators such as Return on Assets (ROA), Return on Equity (ROE), Net Profit Margin (NPM), Net Income, and Debt to Equity Ratio (DER). The analysis results reveal that all profitability indicators experienced a sharp decline, with Net Income even recording negative figures in several post-acquisition periods. Additionally, the increase in DER reflects a higher dependency on debt-based financing, which was not accompanied by improvements in operational efficiency. These findings suggest that the acquisition has not delivered the expected synergy or added value. The study concludes that a reassessment of the post-acquisition strategy is necessary, especially within the highly competitive and capital-intensive telecommunications industry.